Unveiling the Tapestry of Learning: Exploring the Pedagogical Landscape for Transversal and Academic Competencies through the Lived Experiences of School Teachers and Students - Sigdel, Surya; Acharya, Bisna (Nepal Journal of Multidisciplinary Research, 2023)
This research investigates the pedagogical approaches employed for the development of transversal and academic competencies based on the lived experiences of students and teachers. Despite the presence of qualified educators in educational activities, schools face numerous challenges in fully realizing the potential of students. In the context of developing nations like Nepal, schools and teachers encounter unpreparedness in facilitating activities geared towards enhancing students' academic and transversal competencies. Despite teachers' expressed commitment in workshops to adopt student-centered methods, conventional lecture-based approaches persist due to the impact of high-stakes testing. The absence of clear guidelines and motivation further contributes to the prioritization of traditional testing over competency-based education. Furthermore, inadequate facilities and an unsupportive environment hinder the implementation of practice-based education in schools. Recognizing that students excel when engaged in enjoyable activities, it is imperative to align educational activities with learners' needs and interests while progressing towards predefined objectives. This study advocates for a blended management model, incorporating both top-down and bottom-up approaches, to encourage teachers in adopting student-centered methods, thereby playing a pivotal role in nurturing both academic and transversal competencies. Given that both teachers and students tend to prioritize aspects that align with assessment criteria, evaluating assessments covering both competencies become crucial for a comprehensive understanding of their educational progress.